Burden of congenital inguinal hernia and hydrocele in northern and southern Nigeria: An opportunity for awareness creation - Musa Ibrahim; Kabiru Ibrahim Getso; Mohammad Aminu Mohammad (Wolters Kluwer Medknow Publications, 2014)
Background: Nigeria, with a population of >150 million people in which half of the population are children encounters challenges in paediatric surgery practice in rural areas. There are paediatric surgeons in Nigeria, but majority practice in tertiary health facilities in cities. The poor rural dwellers have little or no access to such highly trained specialists. Hence, children with congenital and acquired paediatric surgical pathologies including anterior abdominal wall defects not only grow up with these diseases to adulthood, they are also exposed to various health hazards posed by unqualified personnel. Therefore, we are evaluating the burden of congenital inguinal hernia/hydrocele in northern and southern Nigeria for awareness creation and the way forward. Materials and Methods: Data obtained from organised free hernia missions to the rural populace from northern and southern Nigeria by the West African Collage of Surgeons in 2010 and Kano State Government in 2013 was analysed. Results: A total of 811 patients aged from 3 months (0.25 years) to 35 years was screened and found to have congenital hernia and/or hydrocele from the two centres. 171 (21.1%) were successfully operated, while the remaining 640 (78.9%) could not benefit from a surgical procedure during the missions. There were n = 46 (26.9%) patients with various forms of genital mutilations/and or surgical mismanagements among the operated patients. Conclusion: The burden of congenital anterior abdominal wall defects among Nigerian children is high. A little effort could bring succor and create awareness among this group of people.